Keterkaitan Persepsi Harga, Kemudahan dan Persepsi Manfaat terhadap Keputusan Menggunakan MNC Play pada Konsumen Semarang - Sitti Nurrahmah, Wa Ode; Firdaus; Nurhayati; Effendi, Meizar; Ismanto, Fiderius; Hendriyanto, Asepta; Mulyanto, Kukuh (Business Perspective Journal, 2024)
The internet has become a very basic need for human life in this modern era. This was welcomed by entrepreneurs in this field, various brands have been operating in Indonesia with very varied services. This research aims to describe the relationship between the variables of price perception, convenience, and perceived benefits on the decision to use MNC Play among consumers in Semarang. The population in this research is the MNC Play user community in Semarang. The research sample consisted of 100 respondents who met the sampling criteria (purposive sampling). Data collection was carried out in a structured manner through an instrument (questionnaire) with a Likert scale of 1-10, the data collected was processed with the help of SPSS. The results of this research show that the perception of prices that are classified as competitive can be one of the factors for consumers to use MNC Play products. Apart from that, this research also explains that ease of access and ease of installing Wi-Fi as well as consumers' perceived benefits can be reinforcing factors for consumers. using products from MNC Play (Wi-Fi). In this research, price perception is the thing most highlighted by consumers. This also indicates that people are very sensitive to the price of a product, but this could be a strategy for MNC Play to win business competitions in the internet service (WIFI) sector. Keywords: perception of price, convenience, perception of benefits, decision to use, mnc play (wi-fi)